Theoretical Proposal for the Interweaving of Organizational Development and Lean Manufacturing in Vibrocompressed Manufacturing Companies for Construction. - Chávez Valencia, Luis Elías; Villalobos Pérez, Saúl; Martínez Molina, Wilfrido (HITOS DE CIENCIAS ECONÓMICO ADMINISTRATIVAS, 2024)
The general theory of administration presents various approaches for analyzing and approaching organizations, being the behavioral theory one the most used, since through humanism individuals are prioritized as an essential part of change and the promotion of organizational development. In Mexico, vibrocompressed manufacturing companies in the construction industry generally have a quasi-artisanal production process, which implies an important intervention from the material structure, but also from a social aspect. Reason why, in recent decades Lean Manufacturing is the methodology used, eventhough its tools lack the promotion of human development, which is an organizational catalyst for change, therefor in this documentary research, a theoretical proposal is considered on the overlapping use of Burke-Litwin model during the value chain stage in manufacturing companies in the construction industry, with the goal of promoting a change in human talent that results in an increase to the added value of vibrocompressed products and consequently to profits.